AKTIFITAS FISIK DAN PEKERJAAN TIDAK BERHUBUNGAN DENGAN INDEKS MASSA TUBUH PADA PEREMPUAN USIA 50-60 TAHUN - Abdurahman Berbudi BL (Poltekkes Kemenkes Jakarta III, 2018)
Physical inactivity is an important risk factor for many causes of death, chronic morbidity, and disability. Poor physical activity is also a common world health problem and is a priority of the international health world. Facts are accompanied by clear evidence of an inactivity link to many increased risks of chronic diseases, including heart disease, stroke, and cancer. The purpose of this study was to analyze the relationship between body mass index, physical activity, and occupation in women 50-60 years in Pondok Kelapa Village, Duren Sawit sub-district, East Jakarta. The design of this study is cross-sectional with a total of 130 samples that have been selected by systematic random sampling. The subjects (n = 130) were interviewed using a questionnaire about daily activity in the previous week. Data were analyzed using spss program (Spearman Correlation And Mann Whitney Test). The results of this study indicate that the relationship between physical activity and body mass index is not significant (p = 0.493; p> 0.05; r = 0.61). And the relationship between work and Body Mass Index did not have a significant relationship (p> 0.05). Conclusion: physical activity should be measured and for further research not only interviewed using questionnaires. Keywords : Physical Activity, Body Mass Index, Occupation